Teknik Konseling Islami Dalam Menangani Kenakalan Anak Di Panti Asuhan Putra Muhammadiyah Kota Medan - Adela, Nurul; Sahrul, Sahrul (Kamaya: Jurnal Ilmu Agama, 2024)
Islamic counseling techniques are a continuous, systematic, and purposeful process to help everyone optimize their potential or fitrah by incorporating the values of the Qur'an and Hadith of the Prophet Muhammad in each person. This research aims to explore Islamic counseling techniques in overcoming child delinquency at Putra Muhammadiyah Orphanage in Medan City. This research conducts qualitative research, which interviews, observation, documentation. Furthermore, related to the data sources used by researchers in this study. this data source consists of two parts. primary data sources, secondary data sources. To overcome Child delinquency, caregivers make efforts as follows: teaching religious principles to children and providing guidance, because the hope is that the more they know about religion, the better their behavior will be. Children in orphanages are required to pray and memorize juz 30 or memorize prayers. The management of the Putra Muhammadiyah Medan Orphanage held a recitation and from the results of the research, the conclusion that the concept of Islamic teachings in the context of child education at the Putra Muhammadiyah Medan Orphanage. That each individual has a certain stage of development, and their learning process is influenced by this stage. Discussing the role of Islam as a teaching method, which states that humans are good teachers, but also have passions, guidelines that guide them towards a better future.